2016
DOI: 10.1259/bjr.20151075
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of long-distance running onT2andT2* relaxation times of articular cartilage of the knee in young healthy adults at 3.0 T MR imaging

Abstract: Cite this article as: Behzadi C, Welsch GH, Laqmani A, Henes FO, Kaul MG, Schoen G, et al. The immediate effect of long-distance running on T 2 and T 2 * relaxation times of articular cartilage of the knee in young healthy adults at 3.0 T MR imaging. Br J Radiol 2016; 89: 20151075. FULL PAPERThe immediate effect of long-distance running on T 2 and T 2 * relaxation times of articular cartilage of the knee in young healthy adults at 3. Objective: To quantitatively assess the immediate effect of long-distance run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…That the cartilage of the FPJ reacts initially to a short endurance running burden (30min, 5-10 km run), as well as the FTJ, with a T2( * )-(and T1rho-) decrease, which occurs within a short time (1-2 h) of recovery, could be proven in several studies [26,28,30,70]. However, this response, which is based on a physiological increase in collagen fiber anisotropy and concomitant pressing out of free water from cartilage [31,33,78], could not be detected by our MSUM study and also not in other marathon studies, in which MRI was performed only after several UM stages in a row or 1-2 days after the marathon race, respectively.…”
Section: Cartilage T2 *mentioning
confidence: 92%
See 1 more Smart Citation
“…That the cartilage of the FPJ reacts initially to a short endurance running burden (30min, 5-10 km run), as well as the FTJ, with a T2( * )-(and T1rho-) decrease, which occurs within a short time (1-2 h) of recovery, could be proven in several studies [26,28,30,70]. However, this response, which is based on a physiological increase in collagen fiber anisotropy and concomitant pressing out of free water from cartilage [31,33,78], could not be detected by our MSUM study and also not in other marathon studies, in which MRI was performed only after several UM stages in a row or 1-2 days after the marathon race, respectively.…”
Section: Cartilage T2 *mentioning
confidence: 92%
“…Using magnetic resonance imaging (MRI) -a reliable in vivo method for noninvasive morphological and qualitative assessment of knee cartilage [16][17][18][19][20] -specific volume and thickness (height: Ht) measurement methods with high levels of precision and reproducibility [21][22][23][24][25], as well as post-race T1rho-and T2-relaxation time mapping, have been performed to quantify structure and composition changes in hyaline cartilage on short (5 km) up to long-distance running (marathon) [26][27][28][29][30][31][32][33][34][35]. Both mapping techniques are sensitive to collagen fiber content and network, and to a lesser extent to proteoglycan (PG) changes, showing a high negative correlation with their chondral concentration [36,37], with T2-measurements additionally sensitive to changes of intrachrondral free water content [38].…”
Section: Introductionmentioning
confidence: 99%
“…While every effort was made to commence MRI as soon as possible, T2 postA started nearly 20 min after the run. In comparison, studies that reported significant decreases in T2 commenced data collection b4 min after running [7,9]. The longer period in the current study could have allowed water to migrate back into the cartilage before measurements took place.…”
Section: T1ρ Relaxation Time Values (Ms)mentioning
confidence: 85%
“…T2 postA ). Behzadi et al reported reductions of 12.3-13.2% immediately after a 45-minute run [7], while Subburaj et al noted decreased T2 relaxation times after 30 min of running, albeit only in the medial tibiofemoral compartment (5.4%) [6]. Gatti et al also found that 15 min of running was sufficient to reduce tibial T2 values by 6.1% [9].…”
Section: T1ρ Relaxation Time Values (Ms)mentioning
confidence: 98%
See 1 more Smart Citation